A Systematic Review of the Mechanisms and Outcomes of Compassionate Mind Training - Antika, Eni Rindi; Indreswari, Henny; Hidayah, Nur; Muslihati, Muslihati; Atmoko, Adi; Hotifah, Yuliati; Prabawa, Abi Fa'izzarahman; Menany Soputan, Shania Dea (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2025)
Mental health has become a growing global concern, reflected in the increasing prevalence of psychological disorders worldwide. Compassionate Mind Training (CMT) has gained recognition as an effective intervention to promote psychological well-being. This article investigates the efficacy of CMT, its underlying psychological paradigms, and the limitations of its implementation through a Systematic Literature Review (SLR) based on the PRISMA flow diagram. A total of 96 documents were initially retrieved from the Scopus database, with 12 articles selected following rigorous inclusion and exclusion criteria related to publication year, document type, language, access, population, and context. Findings indicate that CMT significantly enhances self-compassion, reduces stress, anxiety, and burnout, and improves emotional and social functioning. CMT is primarily grounded in a psychological within-paradigm, which emphasizes the integration of internal and external emotion regulation processes. However, several limitations persist, including the absence of a standardized curriculum and difficulties in implementation across diverse cultural and institutional settings. Challenges include fragmented program design and the lack of integration strategies within educational and professional frameworks. The study recommends further research to support cultural adaptation and the development of flexible, evidence-based training models to improve contextual applicability and long-term effectiveness.